POLITICAL AND IDEOLOGICAL EDUCATION FOR UNIVERSITY STUDENTS ON CYBERSPACE - Nguyen Thi Ha Giang (Tạp chí Khoa học, 2025)
In the context of rapid digital transformation and deep international integration, political and ideological education for students in cyberspace has become an urgent task to safeguard the ideological foundation of the Communist Party and to foster political will among the younger generation. This article explores key theoretical aspects of political and ideological education for students in the digital environment, including key concepts, necessity, characteristics, objectives, content, methods, and implementation forms. Based on these analyses, the paper emphasizes the need to innovate educational approaches and effectively leverage cyberspace as a new environment, tool, and means of political and ideological education. It proposes directions for further practical research to enhance the quality of political and ideological education for university students today.